Habituation of Queuing Culture through SIDIA Program to Achieve 21st Century SDGs Goals - Rosid, Suparman; Murferatiwi, Bq. Weddayu; Merpati Dirgantari, Virgynia; Komala Sari, Lina; Endang, Sri; Sumardi, Lalu; Setiadi, Dadi (Lafadz Jaya Publisher, 2024)
This research aims to examine the application of the SIDIA program in forming a queuing culture among elementary school students. Education at the elementary level is an important foundation in developing students' character, including discipline and patience. Observations at one school in Mataram showed that many students did not show good queuing behavior, such as crossing the line when entering class and being impatient when checking assignments. The SIDIA program is implemented both inside and outside the classroom to increase students' awareness of the importance of human culture. In the classroom, the methods used include presenting learning videos that teach character values such as patience and discipline. The results show a significant improvement in student behavior, such as discipline when submitting assignments and shaking hands with teachers outside the classroom. This program also succeeded in creating a more orderly queuing atmosphere, especially in the library, thanks to the use of partitions and attractive slogans. By implementing this program, it is hoped that the culture of queuing can become a habit that is ingrained in students' character, supporting broader and sustainable educational goals. Overall, this research emphasizes the importance of educational character in shaping good social behavior among students and provides recommendations for other schools to implement similar programs in order to achieve SDGs goals in the education sector.